Evaluation of The Organization and Empowerment of Street Vendors Based on Cilegon Mayor Regulation Number 16 of 2018 - Nadya Nur Afina; Yusuf, Maulana; Widyastuti, Yeni (Epistemik Press, 2024)
Street vendors (PKL) are an informal sector that is now often found in various corners of urban areas. The Cilegon City Government has made Regional Regulation Number 6 of 2003 concerning Control of Street Vendors which aims to control and regulate street vendors who sell and set up their businesses so that they comply with the rules determined by the regional government. This Regional Regulation was updated through Cilegon Mayor Regulation Number 16 of 2018 concerning the Management and Empowerment of Street Vendors which focuses more on managing street vendors based on their business permits. This research aims to analyze the evaluation of street vendor control policies in the Pagebangan area of ​​Cilegon City which are reviewed based on Cilegon Mayor Regulation Number 16 of 2018 concerning the Arrangement and Empowerment of Street Vendors. The research uses qualitative descriptive methods. The results of the research show that in material terms the Cilegon Mayor's Regulation Number 16 of 2018 concerning the Arrangement and Empowerment of Street Vendors has met the policy evaluation criteria, so that the regulations relating to the arrangement of street vendors must be maintained in terms of material and objectives. In achieving its objectives, the PKL structuring policy can only meet the criteria of accuracy and requires the activeness of officers to maintain this achievement. Follow-up from the government is in the form of firmness in supervising street vendors to increase the achievement of effectiveness criteria, maturity in planning the physical facilities of street vendors to increase the achievement of efficiency criteria, government openness in conducting guidance for street vendors to increase the achievement of adequacy criteria, data collection and supervision of street vendors to increase achievement of equality criteria, and strengthening cooperation between government agencies to increase the achievement of responsiveness criteria